2014
DOI: 10.1590/1806-9282.60.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are associated with general and central obesity in elderly living in a Brazilian city

Abstract: Objective: dietary pattern evaluation is often used in order to determine wheter a diet is healthy, as well as to predict the onset of diseases. This study aimed to identify dietary patterns, and to examine their associations with general (body mass index) and central (waist circumference and waist-to-hip ratio) obesity in community-living elderly in a Brazilian city. Methods: this cross-sectional study included 126 elderly subjects aged 60 or older (57.1% females and mean age 74.2 ± 6.46 years). Anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(80 reference statements)
0
10
0
1
Order By: Relevance
“…The study was conducted in Botucatu (130,201 inhabitants) (IBGE, 2012) located (22 53 0 09" south latitude, 48 26 0 42" west longitude) in the Sao Paulo state, Brazil. The study consisted in a reevaluation in 2010 (Moment 2010) of a community-living elderly group assessed in 2008 (Moment 2008) (Moreira, Corrente, Boas, & Ferreira, 2014). Two-year follow-up was chosen according to previous study with elderly people (Enoki et al, 2007;Ramos, Simoes, & Albert, 2001) whose results showed that functional decline, anthropometric changes and mortality were correlated in a 2-year period.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in Botucatu (130,201 inhabitants) (IBGE, 2012) located (22 53 0 09" south latitude, 48 26 0 42" west longitude) in the Sao Paulo state, Brazil. The study consisted in a reevaluation in 2010 (Moment 2010) of a community-living elderly group assessed in 2008 (Moment 2008) (Moreira, Corrente, Boas, & Ferreira, 2014). Two-year follow-up was chosen according to previous study with elderly people (Enoki et al, 2007;Ramos, Simoes, & Albert, 2001) whose results showed that functional decline, anthropometric changes and mortality were correlated in a 2-year period.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The corrected arm muscle area (AMAc) was calculated by established formulas (Heymsfield, McManus, Smith, Stevens, & Nixon, 1982). The evaluation of estimated daily intake was performed according to previous study (Moreira, Corrente et al, 2014).…”
Section: Anthropometric Indicators and Dietary Intakesmentioning
confidence: 99%
“…Table 2 shows an overview of the selected studies (n=17), which include 12 cross-sectional2334 and five prospective cohort studies 3539. Except for two studies31,32 using factor analysis, all studies used scoring methods to identify adherence to MDP. Of the 17 articles, 12 reported that the MDP has a preventive effect on obesity 24–33,35,37.…”
Section: The Mdp and Obesitymentioning
confidence: 99%
“…Healthy dietary patterns characterized by increased intakes of fruits and vegetables have been linked to lower risks of cancer, diabetes, cardiovascular disease and Alzheimer's disease, while Western dietary patterns (sugar, fat, processed foods and refined grains) may have the opposite effect. Studies have indicated that dietary patterns can be influenced not only by age, but also by gender, socioeconomic status, marital status, household arrangement, lifestyle and clinical conditions such as disease and mastigation [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%